Recent Research Progress (2015–2021) and Perspectives on the Pharmacological Effects and Mechanisms of Tanshinone IIA - Zhong, Chenhui; Lin, Zuan; Ke, Liyuan; Shi, Peiying; Li, Shaoguang; Huang, Liying; Lin, Xinhua; Yao, Hong (Frontiers in Pharmacology, 2021)
Tanshinone IIA (Tan IIA) is an important characteristic component and active ingredient in Salvia miltiorrhiza, and its various aspects of research are constantly being updated to explore its potential application. In this paper, we review the recent progress on pharmacological activities and the therapeutic mechanisms of Tan IIA according to literature during the years 2015-2021. Tan IIA shows multiple pharmacological effects, including anticarcinogenic, cardiovascular, nervous, respiratory, urinary, digestive, and motor systems activities. Tan IIA modulates multi-targets referring to Nrf2, AMPK, GSK-3β, EGFR, CD36, HO-1, NOX4, Beclin-1, TLR4, TNF-α, STAT3, Caspase-3, and bcl-2 proteins and multi-pathways including NF-κB, SIRT1/PGC1α, MAPK, SREBP-2/Pcsk9, Wnt, PI3K/Akt/mTOR pathways, TGF-β/Smad and Hippo/YAP pathways, etc., which directly or indirectly influence disease course. Further, with the reported targets, the potential effects and possible mechanisms of Tan IIA against diseases were predicted by bioinformatic analysis. This paper provides new insights into the therapeutic effects and mechanisms of Tan IIA against diseases.